Scuola e famiglie immigrate: Uno studio in una scuola del Sud Italia - Marco Centorrino; Lilia Pellegrino (Educatio Siglo XXI, 2020)
Our contribution intends to investigate, in the dimension of everyday life, one of the aspects through which - in our opinion - it is possible to analyze the dynamics of integration of immigrants in Italy.